INHIBITION OF GROUP A STREPTOCOCCUS BY GREEN SYNTHESIZED ZINC OXIDE NANOPARTICLES - AKASH S,; SHANTHA KUMAR SS,; DHAMODHAR P, (International Journal of Pharma and Bio Sciences, 2015)
Group A Streptococcus (GAS), an upper respiratory organism is becoming resistant to antibiotics and nanotechnology has shown tremendous applications as antibacterial agents.In the presentstudy, ZnO nanoparticles were synthesized using Punica granatam epicarp by pyrolysis method. ZnO nanoparticles were characterized by PXRD and were found to have hexagonal phase, wurtzite structure,the crystalline size of the nanoparticle was found to be ~60 nm. The UV-vis spectrum for ZnO nanoparticle showed a strong absorbance at 375 nm corresponding to the band gap energy of 3.25 eV. The FTIR spectrum showed a peak at 499 cm-1, which indicates Zn-O stretch bond. The SEM analysis of Zinc oxide nanoparticles showed the average size of 60 nm and EDS revealed the elemental composition of ZnO nanoparticles ZnO nanoparticles synthesized were tested for their antibacterial activity on GAS and were found to be susceptible.